2018
DOI: 10.1186/s12917-018-1565-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic variability among Pasteurella multocida type A isolates from Brazilian pig farms

Abstract: BackgroundPasteurella multocida type A (PmA) is considered a secondary agent of pneumonia in pigs. The role of PmA as a primary pathogen was investigated by challenging pigs with eight field strains isolated from pneumonia and serositis in six Brazilian states. Eight groups of eight pigs each were intranasally inoculated with different strains of PmA (1.5 mL/nostril of 10e7 CFU/mL). The control group (n = 12) received sterile PBS. The pigs were euthanized by electrocution and necropsied by 5 dpi. Macroscopic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
(47 reference statements)
1
9
1
Order By: Relevance
“…As already addressed, highly pathogenic strains of P. multocida have potential to produce primary lesions of necrohemorrhagic pneumonia, pleuritis, and fibrinous pericarditis (Cappuccio et al 2004. In the present study, polyserositis lesions with isolation of P. multocida were observed in 17 cases (62.9% of polyserositis), sometimes also associated with pneumonia (Paladino et al 2017, Oliveira Filho et al, 2018. Thus, it is suggested that strains of high pathogenicity of P. multocida may be circulating in Brazilian herds, causing mortality and possibly chronic injuries, which can lead to condemnations in slaughterhouses.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…As already addressed, highly pathogenic strains of P. multocida have potential to produce primary lesions of necrohemorrhagic pneumonia, pleuritis, and fibrinous pericarditis (Cappuccio et al 2004. In the present study, polyserositis lesions with isolation of P. multocida were observed in 17 cases (62.9% of polyserositis), sometimes also associated with pneumonia (Paladino et al 2017, Oliveira Filho et al, 2018. Thus, it is suggested that strains of high pathogenicity of P. multocida may be circulating in Brazilian herds, causing mortality and possibly chronic injuries, which can lead to condemnations in slaughterhouses.…”
Section: Discussionsupporting
confidence: 48%
“…Previously, P. multocida was highlighted as a secondary and opportunistic bacterium of the respiratory tract of pigs, mainly related to co-infection with M. hyopneumoniae (Pijoan & Fuentes 1987, Hansen et al 2010. Currently, P. multocida has been also associated with primary lesions of pneumonia and septicemia in pigs (Cappuccio et al 2004, Kich et al 2007, Pors et al 2011, Paladino et al 2017, and it is known to produce suppurative, necrosuppurative and necrohemorrhagic bronchopneumonias, as well as pleurites, especially when there is the involvement of strains of high pathogenicity (Paladino et al 2017, Oliveira Filho et al 2018. In this study, bacterial isolation was possible in 61.30% of bacterial pneumonia cases.…”
Section: Discussionmentioning
confidence: 99%
“…In caesarean‐derived, colostrum deprived pigs, intratracheal and intranasal challenge with P. multocida capsule type A (10 9 organisms) resulted in severe pleuropneumonia, septicaemia and arthritis in the intratracheal group and bronchopneumonia in the intranasal group 39 . In recent studies in Brazil, intranasal inoculation of some but not all isolates of P. multocida capsule type A into conventional pigs resulted in bronchopneumonia, pleuritis, pericarditis and septicaemia at doses that ranged from 10 5 to 10 8 organisms 40,41 …”
Section: Discussionmentioning
confidence: 99%
“…The in vivo efficacy of FF + TAP was also tested in this study. Since A. pleuropneumoniea infections normally produce a clinical manifestation with high mortality rate, intra-tracheal inoculation of P. multocida was used as a clinical pneumonia model (Dowling et al, 2002; Oliveira Filho et al, 2018). While all parameters in the two treatment groups and the two positive control groups showed little or no clinical, histological or biochemical abnormalities after the bacterial challenge, the negative control group showed evidence of severe inflammation/infection.…”
Section: Discussionmentioning
confidence: 99%